The political economy of decarbonisation: from green energy 'race' to green 'division of labour'. Issue 3 (4th May 2017) - Lachapelle, Erick; MacNeil, Robert; Paterson, Matthew
ABSTRACT: This paper aims to provide an addendum to the rapidly growing concept of a global 'green energy race' between major states. It argues that although this framing has been useful in underscoring important dynamics in the process of decarbonisation, its narrow focus on installed capacity obscures a much broader and more complex process at play. In particular, it overlooks the critical role played by states aggressively investing in R&D and export manufacturing in the renewable energy sector. The paper thus supplements the concept of a green 'energy race' with that of a green 'global division of labour', which sees the process of decarbonisation not exclusively as an effort by individual states to install renewables domestically, but rather as a collective and interdependent process by dozens of states, all striving in different ways to promote capital accumulation on their soil. The paper provides an overview of data covering innovation, manufacturing and deployment in the clean energy sector, and offers a theoretical analysis of the trends observed.